Analysis of Sustainable Development of SMEs in Agriculture - BELGIBAYEVA, Anargul; DENISSOVA, Oxana; KOZLOVA, Marina; SAVCHENKO, Irina; TLEUBAYEV, Azat; SIXIMBAYEVA, Gaukhar (Journal of Environmental Management and Tourism, 2022)
The issue of managing the financial stability of SME enterprises is one of the most relevant in modern conditions, since low financial stability can lead to the inability of the enterprise to pay its debts and obligations, as well as to the lack of funds for the development of production (investment, expansion of the material and technical base), and excess can hinder development, burdening the costs of the enterprise with excess (extra) stocks and reserves. The key to minimizing risks, increasing their resilience and competitiveness is essential for many of the world's largest companies to develop and unlock new opportunities. The enterprises of the agro-industrial complex are no exception, given the current conditions for the functioning of the domestic economy, where certain opportunities are created for the development of small and medium-sized businesses, including in the agro-industrial complex, one of which can be noted the provision of state support for the sustainable development of small and medium-sized enterprises at the state level with the adoption a number of national projects and programs. The aim of the study is to analyze the sustainable development of small and medium-sized businesses in the agro-industrial complex through strategic competitive advantages caused by changes that are associated with economic and structural crises in the economy. The result of the study is the identification of problems and ways to solve them.